Reação de porta-enxertos à doença pé-preto e controle biológico de campylocarpon pseudofasciculare em videira - Heckler, Leise Inês (2015)
Black foot disease has described occurrence in most major wine-growing regions of the world. In Brazil, for over a decade researchers have reported the occurrence of the disease in the Serra Gaúcha region. The disease is associated mainly with fungi of the genera Campylocarpon and Ilyonectria. Because these are soil-borne pathogens, their control is limited and little is known about the use of biological products or use of resistant rootstocks. Therefore, the objective of this study was to evaluate commercial products based on Trichoderma spp. and Bacillus spp. in controlling Campylocarpon pseudofasciculare and check the occurrence of resistance in different rootstocks to Campylocarpon pseudofasciculare and Ilyonectria macrodidyma. Tests were carried out in vitro in the Phytopathology Laboratory for Universidade Federal de Santa Maria, in order to verify the efficiency of species of the genera Trichoderma and Bacillus from commercial products in pathogen control, through the method of pairing cultures and volatile metabolites In vivo test was performed in a greenhouse to evaluate the potential for biocontrol of commercial products against the pathogen inoculated in Vitis vinifera seedlings cv. Bordô, grafted on Paulsen 1103. In addition, in the greenhouse, the reaction was studied in rootstocks inoculated with Campylocarpon pseudofasciculare and Ilyonectria macrodidyma. The pairing cultures test with products based on Bacillus spp. and Trichoderma spp. showed an average value of mycelial inhibition growth of 46 and 41%, respectively. In the test of volatile metabolites isolates of Trichoderma spp. better controlled the pathogen, with an average reduction of mycelial growth of 61.5%. In in vivo testing for biocontrol Bacillus subtilis increased the length and dry weight of shoot and all treatments had better parameters than the treatment that received only the pathogen, indicating that these products are able to lessen the severity of the disease on vine plants. In the reaction test, all rootstock proved susceptible to the pathogens.